Impact assessment of Islamic micro-finance on the religious, ethical and social well-being of participants: A case study of Pakistan - Ahmad, Khaliq; Abideen Adeyemi, Adewale; Nauman Khan, Mohamad (IIUM Press, 2017)
Poverty is considered one of the basic problems confronted by the developing and underdeveloped countries of the world including Muslim majority countries like Pakistan. During the last two decades, microfinance institutions have been rapidly established all around the world on the premise that they can alleviate poverty. These institutions open new horizons of economic development. But majority of Muslim populace yearn for Islamic products over conventional microfinance products on account of religious injunctions against paying interest. This paper attempts to analyze the multilevel impact of Islamic microfinance on two Pakistani cities (Multan and Lahore) poor population. This has three dimensions at (i) household level, (ii) enterprise level and (iii) religious, social & ethical levels. Primary data has been collected from the program participants of microfinance institutions in Pakistan, Akhuwat and Wasil Foundations, by employing cross-sectional design with stratified random sampling method. Pearson’s Chi-Square χ2, Yates Continuity Correction, Cramer’s V (φ) and Odds Ratio are used to quantify the difference between established clients (more than one year) and new clients (less than one year). The results of the study support the wide literature on a belief that microfinance can significantly improve the socio-economic and religious status of the participants.